All my secrets - Austin, Lynn N. (Austin, Lynn N. Gilded age, 2024)
When her husband's unexpected death bestows his fortune on a male heir, Sylvia tries to marry her daughter off to a wealthy husband to maintain their lifestyle, but is stopped by her mother-in-law, who wants more for her granddaughter.